University Students' Perspectives on Adopting Internet of Things Technologies in Smart Farming: An Analysis Using the Extended Technology Acceptance Model - Zulfadli Hazim, Zul Azlan; Syahrul Nizam, Junaini; Adnan Shahid, Khan; Wan Azani, Mustafa; Behnam, Ghasemzadeh (John Wiley & Sons, Inc, 2025)
Smart farming leverages advanced technologies to promote sustainable agriculture by reducing carbon emissions, conserving resources and increasing output. At the forefront of this innovation is the Internet of Things (IoT), a network of linked devices enabling efficient monitoring and control of agricultural processes. Despite its benefits, IoT adoption in agriculture remains limited. This pilot study explores factors influencing university students' adoption of IoT technology, as they represent future agricultural innovators. Using an expanded technology acceptance model (TAM) and student survey data, the study identifies key drivers of IoT acceptance in agriculture. The findings provide valuable insights into the factors shaping IoT adoption and offer a foundation for strategies to advance sustainable farming and resource management. This research enriches the existing literature on technology adoption in agriculture. It is a reference for stakeholders aiming to enhance agricultural sustainability and productivity.